2016
DOI: 10.1007/s40090-016-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals by homolytically functionalized poly(acrylic acid) with hydroquinone

Abstract: Poly(acrylic acid) (PAA) was synthesized and chemically modified with hydroquinone (HQ) applying the reaction conditions of Minisci. A degree of modification of as high as 32 % was obtained under optimal conditions: temperature of 70-80°C, time of 5 h, and [p-benzoquinone]/[acrylic acid)] ratio of 1.25. The synthesized PAA and its modified form HQ-PAA were characterized by UV-visible, FT-IR, XRD, SEM, 13 C NMR spectroscopy, TGA, DSC, and size exclusion chromatography. The study of copper (II) adsorption by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The wide humps locating at around 22.5° are due to the existence of binder, polyacrylic acid. [ 52 ] After 1 cycle, the reflection peaks of silicon disappear as shown in Figure 8b, inferring that the crystalline silicon initially transforms to amorphous Li x Si during lithiation, and then the amorphous Li x Si converts to amorphous silicon after fully delithiation. To obtain detailed information of structure evolution during lithiation process, the synchrotron X‐rays diffraction technique was used to investigate the structure evolution of silicon samples with different sizes at four potentials (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…The wide humps locating at around 22.5° are due to the existence of binder, polyacrylic acid. [ 52 ] After 1 cycle, the reflection peaks of silicon disappear as shown in Figure 8b, inferring that the crystalline silicon initially transforms to amorphous Li x Si during lithiation, and then the amorphous Li x Si converts to amorphous silicon after fully delithiation. To obtain detailed information of structure evolution during lithiation process, the synchrotron X‐rays diffraction technique was used to investigate the structure evolution of silicon samples with different sizes at four potentials (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…In Figure b, the crystallization peak of PAA appeared at 31.30° (2θ) . At the same time, the intensity of the crystallization peak at 22.41° (2θ) gradually increased with the increase of the content of CNCs, which indicated that the crystallinity increased.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is seen that LODs of cadmium ion is higher than LODs of copper and lead ions, this fact is in a good correlation with complexing ability of this ion with polymers: cadmium reacts weaker with polymers than lead and copper [42,43].…”
Section: Resultsmentioning
confidence: 99%